2020
DOI: 10.33899/ijvs.2019.125707.1134
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the extended spectrum β-lactamase produced by Escherichia coli from dairy cows by using the Vitek-2 method in Tulungagung regency, Indonesia

Abstract: The use of antibiotics in inappropriate on food producing animals can lead to resistance many of the pathogenic bacteria to the various types of antibiotics, one of which is the Escherichia coli (E. coli) which produces extended spectrum β-lactamase (ESBL). Antibiotic resistance in animals and humans has become a global problem that needs attention and immediate management by using specific antibiotics that used for therapeutic the infected animals. The aim of this study was to isolate and detect E. coli produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 11 publications
4
39
0
Order By: Relevance
“…Some bacteria appears to be resistant to antibiotics, even with maximum doses, according to Janda and Abbot (2010). The resistance of microorganisms to antibiotics develops as resistance to them occurs (Putra et al, 2019). The results showed that A. hydrophila is resistant to gentamicin, streptomycin, tetracycline and amoxicn, which is similar to the results observed by Hazen et al (1978).…”
Section: Clinical Pathologic Examinationsupporting
confidence: 72%
“…Some bacteria appears to be resistant to antibiotics, even with maximum doses, according to Janda and Abbot (2010). The resistance of microorganisms to antibiotics develops as resistance to them occurs (Putra et al, 2019). The results showed that A. hydrophila is resistant to gentamicin, streptomycin, tetracycline and amoxicn, which is similar to the results observed by Hazen et al (1978).…”
Section: Clinical Pathologic Examinationsupporting
confidence: 72%
“…Samples were cultured on Mac Conkey Agar (MCA) media for 24 hours at 37ºC. The bacterial colonies on MCA media were observed for color and texture and processed for identification of E. coli Putra et al 2020).…”
Section: Isolation and Identificationmentioning
confidence: 99%
“…The antibiotic discs of amoxicillin-clavulanic 30μg (Oxoid, England), cefotaxime 30μg (Oxoid, England), ceftazidime 30μg (Becton Dickinson, USA), and aztreonam 30μg (Oxoid, England) were used in this method. Culture was incubated at 35-37ºC for 18-24 hours (Putra et al 2020;CLSI 2017). The inhibition zone that appeared on the cup after incubation was measured based on CLSI guidelines showing an inhibition zone ≤ 27 mm in cefotaxime, inhibition zone ≤ 22 mm in ceftazidime, inhibition zone ≤ 27 mm in aztreonam, and there was a synergy between cefotaxime/ceftazidime with a combination of ≤ 22 mm in ceftazidime, inhibition zone ≤ 27 mm in aztreonam, and there was a synergy between cefotaxime/ceftazidime with amoxicillin-clavulanic in the form of synergy expansion of the inhibition zone between the two disks and there is an increase in the inhibition zone ≥ 5 mm between the diameter of the cephalosporin disk and the cephalosporinclavulanate disk assert that the E. coli bacteria is positive ESBL (CLSI 2017).…”
Section: Esbl Confirmation and Antibiotic Susceptibility Testingmentioning
confidence: 99%
“…Antimicrobial susceptibility and phenotypic detection of ESBL generators were used AST N280 cards (bioMérieux, Marcy-L'Étoile, France). Results were analyzed automatically by the system and interpreted as sensitive, intermediate, and resistant (Brower et al 2017;Biomerioux 2017;Putra et al 2020).…”
Section: Esbl Confirmation and Antibiotic Susceptibility Testingmentioning
confidence: 99%